2019
DOI: 10.1002/advs.201900159
|View full text |Cite
|
Sign up to set email alerts
|

Radiopharmaceuticals and Fluorescein Sodium Mediated Triple‐Modality Molecular Imaging Allows Precise Image‐Guided Tumor Surgery

Abstract: Radical resection is the most effective method for malignant tumor treatments. However, conventional imaging cannot fully satisfy the clinical needs of surgical navigation. This study presents a novel triple‐modality positron emission tomography (PET)–Cerenkov radiation energy transfer (CRET)–confocal laser endomicroscopy (CLE) imaging strategy for intraoperative tumor imaging and surgical navigation. Using clinical radiopharmaceuticals and fluorescein sodium (FS), this strategy can accurately detect the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Recent studies reported that diabetes could contribute to the development of cancer via inflammation, and thus has been identified as a risk factor for cancer and cancer-related mortality [ 36 , 37 ]. Malignant tumors such as hepatocellular carcinoma and breast cancer are important causes of human death, and a significant link between them and diabetes has been evidenced [ 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported that diabetes could contribute to the development of cancer via inflammation, and thus has been identified as a risk factor for cancer and cancer-related mortality [ 36 , 37 ]. Malignant tumors such as hepatocellular carcinoma and breast cancer are important causes of human death, and a significant link between them and diabetes has been evidenced [ 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] Ultrasonography (US) Ref. 17 Photodynamic therapy (PDT) Ref. [31][32][33][34][35][36][37][38][39] Magneto-acoustic imaging (MAI) Ref.…”
Section: Image-based Diagnosismentioning
confidence: 99%
“…15 ) with PBCA, an FDA-approved biomaterial, which exhibited prolonged life-time and excellent stability due to the polymeric shell preventing gas core from shrinkage. 17 With the in situ one-pot polymerization, a narrowly distributed and monodispersed population of MBs could be afforded, and provide a real-time visualization for discriminating versatile processes of molecular imaging, MB disintegration, and drug release from MBs as drug payloads. Thus, it may be used for image-guided surgery and achieve high efficiency of synergistic treatments combining ultrasound and these polymeric MBs.…”
Section: Noninvasive Disease-oriented Diagnostic Modalitymentioning
confidence: 99%
“…Cheng's team reported an α v β 3 integrin-targeted PET/NIR II nanoprobe ( 68 Ga-SCH2) for tumor delineation and targeting IGS. [236][237][238][239][240][241][242][243] compared with FGS using ICG, in subcutaneous breast cancer 4T1 tumor, orthotopic, and orthotopic-ectopic hepatocellular carcinoma tumor models. [235] CL imaging (CLI) has been successfully used for LN mapping and IGS in animal models.…”
Section: Pet/spect/ct-based Multimodal Imagingmentioning
confidence: 99%
“…[235] CL imaging (CLI) has been successfully used for LN mapping and IGS in animal models. [236] CRET can convert the ultraviolet/blue-weighted light from CL to longer wavelength. [239] Recently, the same group developed a kind of triple-modal molecular imaging combining PET, Cerenkov radiation energy transfer (CRET), and confocal laser endomicroscopy (CLE), called PET-CRET-CLE imaging.…”
Section: Pet/spect/ct-based Multimodal Imagingmentioning
confidence: 99%